Hereditary Colorectal Tumors: A Literature Review on MUTYH-Associated Polyposis. (25th September 2017) - Kantor, Micaella; Sobrado, Javier; Patel, Sima; Eiseler, Sara; Ochner, Christopher
Abstract : MAP (MUTYH-associated polyposis) is a syndrome, described in 2002, which is associated with colorectal adenomas, with enhanced colorectal carcinogenesis. This review synthesizes the available literature on MAP and outlines its pathogenesis, association with colorectal tumorigenesis, screening, treatment, and the subtle differences between it and its close cousins—FAP and AFAP. The preponderance of data is collected using MAP guidelines. However, although AFAP and MAP appear similar, potentially important distinctions exist, warranting targeted diagnostic criteria and treatment approaches. We suggest that it may be prudent to screen for MAP earlier than in current clinical practice, as it has been shown that sequence variants are associated with more severe disease, presenting with an earlier onset of colorectal cancer. Finally, we issue a call-to-action for much-needed further data to establish clear clinical and diagnostic criteria.